2022
DOI: 10.1002/cssc.202200181
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Routes for Designing Furanic and Non Furanic Biobased Surfactants from 5‐Hydroxymethylfurfural

Abstract: This publication is part of a collection of invited contributions focusing on "Green Conversion of HMF". Please visit chemsuschem.org/collections to view all contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…59 Pt/SiO 2 catalyst in neutral solution and Pt–ZrO 2 in acidic solution could efficiently oxidize HMF to DFF with high yield under aerobic conditions. 60 Taarning et al 61 reported that the oxidation of HMF over Au/TiO 2 catalyst in MeOH could produce dimethyl furan-2,5-dicarboxylate (DFD) in excellent yield at 130 °C under basic conditions. Skowronski et al 62 proposed that DFF could also be obtained through the electrochemical oxidation of HMF using biphasic H 2 O–CH 2 Cl 2 solvent in a divided cell equipped with a Pt anode.…”
Section: Upgrading Of Hmf To Fuels and Value-added Chemicalsmentioning
confidence: 99%
“…59 Pt/SiO 2 catalyst in neutral solution and Pt–ZrO 2 in acidic solution could efficiently oxidize HMF to DFF with high yield under aerobic conditions. 60 Taarning et al 61 reported that the oxidation of HMF over Au/TiO 2 catalyst in MeOH could produce dimethyl furan-2,5-dicarboxylate (DFD) in excellent yield at 130 °C under basic conditions. Skowronski et al 62 proposed that DFF could also be obtained through the electrochemical oxidation of HMF using biphasic H 2 O–CH 2 Cl 2 solvent in a divided cell equipped with a Pt anode.…”
Section: Upgrading Of Hmf To Fuels and Value-added Chemicalsmentioning
confidence: 99%
“…Thus, dehydration of pentoses or hemicellososes yields furfural while corresponding transformations of hexoses lead to hydroxymethylfurfural (HMF). These compounds are currently studied in connection with the production bulk products such as new polymers [ 194 , 197 ] or surfactants [ 198 , 199 , 200 ].…”
Section: Biomass-derived Platform Chemicalsmentioning
confidence: 99%
“…, furosemide). 3 The synthesis of furfurylamines can be conducted from FF and 5-hydroxymethylfurfural (HMF) by direct/reductive amination over homogeneous and heterogeneous catalysts. 4 Also, secondary and tertiary tetrahydrofurfurylamines can be accessed with high yield (>90%) from FF over Pd/Al 2 O 3 at room temperature and 1 bar H 2 .…”
Section: Introductionmentioning
confidence: 99%